PELATIHAN DAN PENDAMPINGAN SENAM LANSIA DI PAKMONTI (PASAR KREATIF MONUMEN PONCOWATI) PONCOWATI, LAMPUNG TENGAH - Rina Wahyuni; Setianingsih Setianingsih; Fahrul Irayani; Efa Septiana; Weda Ayu Ardini; Ekta Puspita Sari; Dody Triolandi; Erika Yuliani; Tri Ayu Agustian; Anggi Aprilia; Ikhsan Andini; Rizka Dwi Saputri; Linda Wanudiah (Jurnal Abdi Insani, 2022)
According to the Ministry of Health, the decline in elderly health is a natural process experienced when a person enters the age of 60 years and over. This decline in fitness can occur due to the lack of complete nutrition consumed and the lack of physical activity carried out. This community service activity aims to determine whether the implementation of elderly gymnastics that is applied to the elderly and carried out regularly can improve the fitness of the elderly in PAKMONTI, Poncowati, Terbanggi Besar, Central Lampung. The method used in this activity is to provide exercise training for the elderly. This training is carried out according to the PAKMONTI schedule, namely on Sunday mornings. The implementation of the introduction and training of elderly gymnastics is that the lecturer and students provide examples of light and easy elderly gymnastics for the elderly. The results of these community service activities are that the elderly feel more fit with these activities and feel happy to do gymnastics. Physical movements performed during gymnastics are also very light and adapt to the abilities of the elderly who have limitations for physical activity. In this activity, the elderly looked so happy and happy because at the end of the gymnastics activity, the elderly received prizes from coupons that had been provided by the activity implementation committee. Prize coupons provided by the committee were drawn at random, the forms of prizes given to participants were also varied so that the elderly seemed very happy to participate in this activity to the end. This community service activity in the form of implementing elderly gymnastics is very helpful for the community, especially the elderly in PAKMONTI, Poncowati, Terbanggi Besar, Central Lampung in improving their physical fitness.